Optimum Growth and Carbon Policies with Lags in the Climate System - Lucas Bretschger; Christos Karydas (ETH Zurich, CER-ETH - Center of Economic Research, 2017)
We study the effects of greenhouse gas emissions on optimum growth and environmental policy by using an expansion-in-varieties growth model with polluting non-renewable resources. Climate change harms the capital stock. Our main contribution is to introduce and extensively explore the naturally determined time lag between greenhouse gas emission and the damages due to climate change which proves to be crucial for the transition of the economy towards its steady state. The social optimum and optimal abatement policies are fully characterized. The inclusion of a green technology delays optimal resource extraction. The optimal tax rate on emissions is proportional to output. Poor understanding of the emissions diffusion process leads to suboptimal carbon taxes and suboptimal growth and resource extraction.
Keywords: Q54; O11; Q52; Q32; 330; Climate Policy; Non-Renewable Resource Dynamics; Pollution Diffusion Lag; Optimum Growth; Treibhausgas-Emissionen; Optimales Wachstum; Klimapolitik; Erschöpfbare Ressourcen; Umweltbelastung; Ökosteuer; Endogenes Wachstumsmodell